125 Sex differences in myocarditis natural history. (8th December 2021) - Castrichini, Matteo; Merlo, Marco; Baggio, Chiara; Gagno, Giulia; Maione, Davide; Porcari, Aldostefano; Barbati, Giulia; Adamo, Luigi; Mestroni, Luisa; Sinagra, Gianfranco
Abstract: Aims: The role of sex in determining the profile and the outcomes of patients with myocarditis is widely unexplored. Our study seeks to evaluate the impact of sex as a modifier factor in the clinical characterization and natural history of patients with definite diagnosis of myocarditis. Methods and results: We retrospectively analysed a single-centre cohort of consecutive patients with definite diagnosis (i.e., endomyocardial biopsy or cardiac magnetic resonance proven) of myocarditis. A sub-analysis was performed after division of population according to the main symptom of presentation (i.e., chest pain, ventricular arrhythmias, and heart failure). Clinical and echocardiographic data were evaluated at diagnosis and at last available evaluation (i.e., median of 30 months). The study outcome measure was a composite of all-cause mortality or heart transplantation. We enrolled 312 patients (187; 60% presenting with chest pain; 19; 6% with ventricular arrhythmias; 106; 34% with heart failure). Most of patients (211, 68% of the whole population) were males, consistently in the three modes of presentation. Despite no clinically relevant differences were found at baseline presentation, males presented a larger indexed left ventricular end-diastolic volume (LVEDVi) (62 ± 23 vs. 52 ± 20, P = 0.011 in males vs. females respectively) at follow-up evaluation. At a median follow-up of 62 months, 36 (17%) males vs. females experienced death or heart transplantation (Log-rank P = 0.037). At multivariable Cox analysis, male sex emerged as a predictor of mortality (HR: 2.358; 1.044–5.322; P = 0.039 and left ventricular ejection fraction (LVEF) < 50% (HR: 8.169; 1.226–54.425; P = 0.030)]. Results were consistent in patients presenting with heart failure and chest pain, while arrhythmic group was too small to be reliably interpreted. Conclusions: In a large cohort of patients with definite diagnosis of myocarditis, females experienced a more favorable long-term prognosis than male, despite a similar clinical profile at baseline.